Investigation of the Influence of Reduced Graphene Oxide Flakes in the Dielectric on Surface Characteristics and Material Removal Rate in EDM - Świercz, Rafał (Materials (Basel), 2019)
Electrical discharge machining (EDM) is an advanced technology used to manufacture difficult-to-cut conductive materials. However, the surface layer properties after EDM require additional finishing operations in many cases. Therefore, new methods implemented in EDM are being developed to improve surface characteristics and the material removal rate. This paper presents new research about improving the surface integrity of 55NiCrMoV7 tool steel by using reduced graphene oxide (RGO) flakes in the dielectric. The main goal of the research was to investigate the influence of RGO flakes in the dielectric on electrical discharge propagation and heat dissipation in the gap. The investigation of the influence of discharge current I and pulse time t(on) during EDM with RGO flakes in the dielectric was carried out using response surface methodology. Furthermore, the surface texture properties and metallographic structure after EDM with RGO in the dielectric and conventional EDM were investigated and described. The obtained results indicate that using RGO flakes in the dielectric leads to a decreased surface roughness and recast layer thickness with an increased material removal rate (MRR). The presence of RGO flakes in the dielectric reduced the breakdown voltage and allowed several discharges to occur during one pulse. The dispersion of the discharge caused a decrease in the energy delivered to the workpiece. In terms of the finishing EDM parameters, there was a 460% reduction in roughness Ra with a uniform distribution of the recast layer on the surface, and a slight increase in MRR (12%) was obtained.